Flexible all-solid-state asymmetric supercapacitor based on three-dimensional MoS2/Ketjen black nanoflower arrays. (21st May 2019) - Zhao, Yunhe; He, Xinyi; Chen, Rongrong; Liu, Qi; Liu, Jingyuan; Yu, Jing; Zhang, Hongsen; Dong, Hongxing; Zhang, Milin; Li, Rumin; Wang, Jun
Abstract: High electrochemical properties of negative electrode materials are highly desirable for flexible asymmetric supercapacitors (ASCs). Although benefiting from the unique structure and broad operation potential, molybdenum disulfide (MoS2 ) has caused concern as a negative electrode material because its low electrochemical stability and poor conductivity hinder the exploitation of its application in flexible ASCs. Here we investigated a facile two-step hydrothermal approach to fabricate MoS2 /Ketjen black (KB) composites on flexible carbon cloth. Following the construction of flower-like MoS2 on carbon cloth, KB nanospheres were embedded in MoS2 via a secondary hydrothermal route. The as-prepared MoS2 /KB electrode presents a high capacitance of 429 F g −1 at a current specific of 1 A g 1 . In addition, the hybrid ASC device of NiCo2 O4 //MoS2 /KB was built, which delivers a high energy density of 25.7 Wh kg −1 and power density of 16 kW kg −1 . These results are ascribed to the favorable structure of MoS2 and inherently superior conductivity of KB, which improves wettability, structural stability and electronic conductivity. In brief, the proposed all-solid-state ASC device offers potential application in future portable electronics and flexible energy storage devices. Graphical abstract: Image 1 Highlights: Flower-like structure of MoS2 /KB is prepared as flexible supercapacitor electrode. The MoS2 /KB electrode exhibits remarkable specific capacitance and cycling stability. A flexible all-solid-state ASC device based on MoS2 /KB is fabricated. The enhanced performance is attributed to the favorable structure of MoS2 and conductive KB skeleton.